Innovation of Higher Order Thinking Skills (HOTS)-based Assessment in Balaghoh Learning: Inovasi Penilaian berbasis HOTS dalam Pembelajaran Balaghoh - Alma Melati; Rahil Ayu Na Ziihah; Agung Setiyawan (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2024)
Assessment of balaghoh learning in universities is still in the category of low-level thinking skills. The test instruments still ask for understanding, the number of types, and other basic questions. This research aims to provide an innovative test based on Higher Order Thinking Skills (HOTS) for assessing balaghoh learning at the Islamic Religious College (STAI) Masjid Syuhada Yogyakarta. This field research is qualitative, with a case study type. Data collection methods include interviews, observations, focus group discussions, and documentation. The results of this study indicate that the Balaghoh assessment instrument used has implemented HOTS cognitive level tests. However, there are only 3 test items that are included in the HOTS domain. This shows the limited number of HOTS items used in the assessment. Through this study, the researcher innovated a test instrument containing 14 HOTS items to test students' ability to analyze and evaluate sentence structure from the perspective of balaghoh science and create kalām-kalām (baligh) according to instructions. The innovation of this test instrument is explained with a description of the implementation of each item that contains the HOTS cognitive domain so that it can be understood and used for the development of balaghoh test instruments. Abstrak Penilaian pembelajaran balaghoh di perguruan tinggi masih dalam kategori kemampuan berpikir tingkat rendah. Instrumen tes masih menanyakan pengertian, jumlah jenis dan pertanyaan dasar lainnya. Penelitian ini bertujuan untuk memberikan inovasi tes berbasis HOTS dalam menilai pembelajaran balaghoh di Sekolah Tinggi Agama Islam Syuhada (STAI) Masjid Yogyakarta. Penelitian lapangan ini bersifat kualitatif dengan jenis studi kasus. Metode pengumpulan data melalui wawancara, observasi, diskusi kelompok terkhusus, dan dokumentasi. Hasil penelitian ini menunjukkan bahwa instrumen penilaian balaghoh yang digunakan telah menerapkan tes tingkat kognitif HOTS. Namun hanya terdapat 3 butir soal tes yang masuk dalam ranah HOTS. Hal ini menunjukkan terbatasnya butir soal HOTS yang digunakan dalam penilaian. Melalui penelitian ini, peneliti membuat inovasi instrumen tes yang memuat 14 butir soal HOTS untuk menguji kemampuan mahasiswa dalam menganalisis dan mengevaluasi struktur kalimat dengan prespektif ilmu balaghoh dan menciptakan kalām-kalām (baligh) sesuai instruksi. Inovasi instrumen tes ini dijelaskan dengan gambaran pelaksanaan setiap butir soal yang memuat ranah kognitif HOTS sehingga dapat dipahami dan digunakan untuk pengembangan instrumen tes balaghoh.